The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1163/156856299x00621
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-derived bioadhesives for closing skin wounds: An in vivo study

Abstract: Bioadhesives have been used in surgery as hemostatic and wound healing agents. GRF (gelatin + resorcinol + formaldehyde) glue, composed of a mixture of gelatin and resorcinol polymerized by the addition of formaldehyde, has been used for this purpose. Widespread acceptance of the GRF glue, however, has been limited by reports of cytotoxicity due to its release of formaldehyde upon degradation. It has been suggested by Wertzel et al. that the cytotoxicity problem of GRF glue may be overcome by changing its cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The in vitro and in vivo toxicity of crosslinked genipin has been reported to be minimal and significantly lower than the toxic level of more popular crosslinkers, such as glutaraldehyde [23][24][25][26]. These reports are consistent with our in vitro cytotoxicity study, as media extracted from BSAgenipin solders that underwent thermal treatment did not inhibit significantly the growth of murine fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…The in vitro and in vivo toxicity of crosslinked genipin has been reported to be minimal and significantly lower than the toxic level of more popular crosslinkers, such as glutaraldehyde [23][24][25][26]. These reports are consistent with our in vitro cytotoxicity study, as media extracted from BSAgenipin solders that underwent thermal treatment did not inhibit significantly the growth of murine fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Gelatin, which is essentially denatured collagen, has a myriad of uses in the food, pharmaceutical and cosmetic industries [9]. As for the genipin, it is a naturally occurring and low-cytotoxic crossing agent, which can be obtained from its parent compound geniposide isolated from the fruits of Gardenia jasminoides ELLIS [10,11]. In the present study, we describe the synthesis of the genipin-cross-linked gelatin conduit (GGC).…”
Section: Introductionmentioning
confidence: 99%
“…17 The feasibility of using genipin to crosslink gelatin as a novel biological glue to close skin-wound lesions has been previously evaluated in vitro and in vivo in a rat model. 18,19 Formaldehyde and glutaraldehyde were used as controls. The results showed that the cytotoxicity of the genipin-crosslinked glue was significantly less than the aldehyde-crosslinked glues.…”
Section: Introductionmentioning
confidence: 99%